2013
DOI: 10.1371/journal.pgen.1003394
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Gene Expression Analysis Identifies CD84 as a Predictor of Response to Etanercept Therapy in Rheumatoid Arthritis

Abstract: Anti-tumor necrosis factor alpha (anti-TNF) biologic therapy is a widely used treatment for rheumatoid arthritis (RA). It is unknown why some RA patients fail to respond adequately to anti-TNF therapy, which limits the development of clinical biomarkers to predict response or new drugs to target refractory cases. To understand the biological basis of response to anti-TNF therapy, we conducted a genome-wide association study (GWAS) meta-analysis of more than 2 million common variants in 2,706 RA patients from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 38 publications
4
121
1
1
Order By: Relevance
“…The DANBIO (Danish Biologics Database) register also suggested that older age and use of oral prednisolone are predictors of poor response (Hetland et al, 2010), but this was not seen in other registry data ). An increasing number of single nucleotide polymorphisms associated with clinical response to TNF inhibitors are being identified (Cui et al, 2013;DavilaFajardo et al, 2014). These require extensive further validation and are not currently of clinical utility.…”
Section: A Anti-tumor Necrosis Factor Drugs In Rheumatoid Arthritismentioning
confidence: 99%
“…The DANBIO (Danish Biologics Database) register also suggested that older age and use of oral prednisolone are predictors of poor response (Hetland et al, 2010), but this was not seen in other registry data ). An increasing number of single nucleotide polymorphisms associated with clinical response to TNF inhibitors are being identified (Cui et al, 2013;DavilaFajardo et al, 2014). These require extensive further validation and are not currently of clinical utility.…”
Section: A Anti-tumor Necrosis Factor Drugs In Rheumatoid Arthritismentioning
confidence: 99%
“…We identified three published studies that identified SNPs associated with anti-TNF-response (11)(12)(13), as well as the results from the winning algorithm at the recent Rheumatoid Arthritis Responder Challenge, developed by team GuanLab, University of Michigan (https://www.synapse.org/#!Synapse:syn2504648). Altogether 52 potentially anti-TNF-response associated Figure S2).…”
Section: Genetic Associations With Anti-tnf-responsementioning
confidence: 99%
“…Integration of known DnA, rnA and Protein Biomarkers Provides Prediction of Anti-TnF response in rheumatoid Arthritis: results from the CoMBIne study Lasse Folkersen,1,2 Boel Brynedal, 3 Lina Marcela Diaz-Gallo, 2 Daniel Ramsköld, 2 Klementy Shchetynsky, 2 Helga Westerlind, 3 Yvonne Sundström, 2 Danika Schepis, 2 Aase Hensvold, 2 Nancy Vivar, 2 Maija-Leena Eloranta, 4 Lars Rönnblom, 4 Søren Brunak, 1 (11)(12)(13) and proteomics (14), as well as better use of clinical data (15) to predict treatment response, particularly for TNF blockade. Success has been limited with virtually no findings validated in independent material, and no biomarker for prediction of response is currently used in clinical practice (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that address this at the level of genetic variation have proved challenging to perform, tending to suffer as a result of insufficient power, differing definitions of therapeutic efficacy, confounding factors or a combination thereof [13]. A few seemingly robust findings include association between the reduced folate carrier 1 variant and methotrexate efficacy [14] and between the 1q23 locus and etanercept efficacy (with the CD84 gene being functionally implicated) [15]. Moving forward concerted efforts must be made to collate large cohorts of RA patients, better characterized for multiple clinical covariates, in order that high-powered and optimally controlled GWASs might identify robust predictors of therapeutic efficacy.…”
Section: Precision Medicine?mentioning
confidence: 99%